Pendampingan Advokasi Hak Kesehatan Terhadap Korban Pelanggaran HAM Berat Lansia Tahun 1965 di FOPPERHAM Yogyakarta. - Nirwani Mintanawati; Siswanto Siswanto (Mafa Press, 2023)
The purpose of the study are to find out which way done fopperham advocacy and shape the success of done fopperham 1965 human rights to the victim. The research is research field research namely research who takes primary data in the field, in the location. Studi field work was carried out by selecting fopperham institutions in Yogyakarta. While the types and approach research used in this research was descriptive qualitative, because in this research produce conclusions in the form of who described in detail, which is in the form the figures is not data. The result of the research indicated. First, violations of human rights on a victim advocacy fopperham heavy 1965 it can be seen from a number of ways, ranging from reading park give education, give the shape of advocacy of a policy of, and give the shape of health services. Second, the form of the success of fopperham in engage in advocacy of clients can be seen from micro approach, mezzo, and macro.It is held to find out the form of the success of conducted by fopperham.